Logging On: Using Online Learning to Support the Academic Nomad - Gargano, Terra; Throop, Julia (Journal of International Students, 2017)
The Internet is cited for bringing about the most rapid and significant social change within societies worldwide. Higher education does not lie at the fringe of this discussion, but is rather at the center of it. Online learning is no longer considered a mere supplement to education but digital tools now routinely embed themselves in higher education spaces. The evolving modalities of online learning are expanding the terrain of academic possibilities farther than previously imagined and new educational technologies are introduced daily. Against a backdrop of the potential for online learning in higher education, this article will paint a portrait of the ways one graduate program at a United States institution of higher education is addressing demands of academic nomads.